Peran Penyuluh Pertanian dalam Program Youth Entrepreneurship and Employment Support Services (YESS) di Kabupaten Pacitan - Rahma, Daning Luthfiah; Sugihardjo, Sugihardjo; Rusdiyana, Eksa (Fakultas Pertanian Universitas Jember, 2024)
The agricultural sector is faced with the challenge of lack of human resource regeneration due to the low interest of the younger generation to pursue agriculture. One of the government's efforts to support the regeneration of farmers is by increasing interest in agricultural entrepreneurship through the Youth Entrepreneurship and Employment Support Services (YESS) Program in collaboration with various parties, one of which is agricultural extension agents. The purpose of this study was to analyze the role of agricultural extension agents and identify the supporting aspects and inhibiting aspects of agricultural extension agents in the implementation of the YESS program in Pacitan District. The basic method of this research is descriptive qualitative with a purposive and snowball method of determining informants with a total of 25 people. Data collection techniques by means of in-depth interviews, observation, and documentation and using Miles and Huberman interactive data analysis techniques. Data validity uses triangulation of sources and techniques. The results showed that agricultural extension agents in the YESS program in Pacitan District overall carried out their roles as educator, motivator, facilitator, innovator, consultant, and communicator with good categories, while for the role of evaluator in the category was quite good because agricultural extension agents were not involved in organizing evaluations directly, but the evaluation was carried out by the Monitoring and Evaluation Team from the District Implementation Team (DIT) and the Provincial Project Implementation Unit (PPIU). Supporting aspects for the role of agricultural extension agents are the good quality of agricultural extension human resources, the high motivation of the younger generation, and the support of various stakeholders. While inhibiting aspects are inadequate BDSP / BPP facilities, the lack of agricultural extension human resources, and the absence of agricultural extension duties related to the YESS program.